Pendampingan Pengisian dan Pelaporan SPT Tahun PPh Wajib Pajak Orang Pribadi dengan Menggunakan E-Filling - Umar Yeni Suyanto; Rita Nataliawati; Laelatul Zahro (Jurnal Pengabdian Masyarakat Nusantara, 2025)
In principle, every individual who fulfills his subjective and objective obligations is obliged to register himself as a Taxpayer (WP) based on the "self assessment" system. When someone registers personally, they will get a Taxpayer Identification Number (NPWP), which consists of 15 certain digits that only the WP concerned has. General tax obligations for Individual Taxpayers (WPOP) are calculating Income Tax (PPh) for one year and depositing income tax with a Tax Payment Slip (SSP) if there is an underpayment of income tax and reporting taxes through the Annual Personal Tax Return (SPT). ). Today the Directorate General of Taxes has made it easy for all taxpayers, especially individual taxpayers to submit their SPT via E-Filing, namely electronic SPT submission which can be done online and in real time. Lamongan Accounting Vocational School located on di Jalan Sunan Giri LTC Blok.B No.16, Lamongan has 32 teachers and 675 students. This school has 4 majors namely Computer Network Engineering (TKJ), Office Administration, Banking and Accounting. At this school there are no teachers who can do their own annual SPT reporting using e-filling because they are used to reporting directly to the DGT. Therefore we want to help teach annual tax returns using this e-filling so that they can do their own tax reporting. The method of carrying out this activity is to give lectures on the meaning of taxation and training in filling out tax returns (SPT) via e-filling. The result of this activity is to increase the understanding of Lamongan Accounting Vocational School teachers about the obligation to report taxes and report SPT for individual taxpayers by e-filing.